Electricity from saccharide-based galvanic cell - Mophan Nattinee; Poonsawat Thinnaphat; Chumkaeo Peerapong; Somsook Ekasith (Chemistry Teacher International)
Here we report a practical laboratory that first-year undergraduate students can do in a general chemistry framework to explore both electrochemistry and transition metal chemistry. These laboratory activities focus on the use of saccharides and specifically starch as possible sustainable sources of energy by experimenting with the redox reactions that occur between vanadate ions and different saccharides. Students undergo hands-on experiments in order to see color changes that indicate electron transfer and link to real-world applications of these concepts in energy conversion. To reduce dependency on foreign resources and the economic risks of foreign energy product prices, the experiments employed agricultural products to generate electricity. Through the application of “Sufficiency Economy” philosophy, this work provides students with lessons in sustainable practice and the fundamentals of electrochemistry, which are essential for addressing today’s global challenges.